2011
DOI: 10.1039/c0sm01324b
|View full text |Cite
|
Sign up to set email alerts
|

UCST-type behavior of poly[oligo(ethylene glycol) methyl ether methacrylate] (POEGMA) in aliphatic alcohols: solvent, co-solvent, molecular weight, and end group dependences

Abstract: Poly[oligo(ethylene glycol) methyl ether methacrylate] (POEGMA) is shown to possess insoluble– soluble transitions (UCST-type phase behavior) in a large variety of aliphatic alcohols. Samples of different molecular weights ranging from 5 kg mol1 to 23 kg mol1 prepared by the RAFT process and featuring different end groups at each end were analyzed by cloud point measurements. Transitions occurred sharply and were fully reversible. The UCST was found to increase with an increasing molecular weight. Hydrophobic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
140
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(156 citation statements)
references
References 46 publications
15
140
0
1
Order By: Relevance
“…Thermal relaxation back to the trans form results in the polymers regaining their cloud point from prior to irradiation within 24h. Similarly to reports by Roth et al 33 , our tegylated poly(azocalix [4]arene)s and poly(azodibenzo-18-crown-6-ether)s showed strong dependence of the cloud point on water content within the alcohol sample. In the first case, minimal addition (0.5% v/v) of water to a polymer fraction AZTEGOMe20 in ethanol (2.5 g/L) resulted in a shift of the demixing temperature by 10°C.…”
Section: Fig 34supporting
confidence: 54%
See 2 more Smart Citations
“…Thermal relaxation back to the trans form results in the polymers regaining their cloud point from prior to irradiation within 24h. Similarly to reports by Roth et al 33 , our tegylated poly(azocalix [4]arene)s and poly(azodibenzo-18-crown-6-ether)s showed strong dependence of the cloud point on water content within the alcohol sample. In the first case, minimal addition (0.5% v/v) of water to a polymer fraction AZTEGOMe20 in ethanol (2.5 g/L) resulted in a shift of the demixing temperature by 10°C.…”
Section: Fig 34supporting
confidence: 54%
“…In the past, systems based on poly(methyl methacrylate), PMMA 31 , poly(2-oxazolines) 32 and copolymers of hydroxyethyl methacrylate and acetoacetoxyethyl methacrylate in ethanol/water mixtures have also demonstrated the UCST-behaviour. Recently, poly(oligoethyleneglycol) methacrylate, POEGMA has been shown to undergo the UCST-type transitions in alcohols, which are strongly dependent on the degree of polymerization, concentration, alcohol and end groups 33 .…”
Section: Thermo-responsive Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 34 ] Roth et al showed that POEGMA based copolymers also exhibit a UCST behavior in alcohol/ water mixtures. [ 35,36 ] Hu and Paris et al prepared organic cross-linker cross-linked P(MEO 2 MA -co-OEGMA) hydrogels, which featured a controllable LCST depending on the monomer molar ratio. [ 37,38 ] Different from the previous linear polymers or thermosenstitive hydrogels, both of which exhibit only one UCST or LCST and have been reported extensively, we recently developed a series of clay/P(MEO 2 MA -co-OEGMA) nanocomposite (NC) hydrogels featuring double volume phase transition temperatures (UCST and LCST).…”
Section: Introductionmentioning
confidence: 98%
“…Recently, oligo(ethylene glycol) methacrylate (OEGMA) based polymers have gained increasing attention because of their biocompatibility and adjustable VPTT [24][25][26]. Lutz et al first reported the thermosensitive copolymers by copolymerization of 2-(2-methoxyethoxy) ethyl methacrylate (MEO 2 MA) and OEGMA units, showing obvious advantages such as non-toxicity, narrow hysteresis, and precisely tunable VPTT between 20 and 80°C, which could be adjusted by the length of the side chains and the copolymer composition [27][28][29].…”
Section: Introductionmentioning
confidence: 99%